Democratic Election of Noken in Papua (Law Research Review Quarterly, 2018)
The holding of General Elections in some parts of Papua has its own character because its implementation is different from General Elections in general. If all this time we only know that the General Elections are held "Directly, Publicly, Freely, and Secretly", then there are some areas in Papua that still use the General Election with the noken and / or connective system. This is because the culture of the indigenous Papuan people in terms of decision making concerning the common interest is done through a deliberation meeting by involving the community as a whole or certain people ("Men of Authority" or "The Big Man") alone as representatives to make decisions. This was also strengthened by the Constitutional Court's Decision which essentially stated that it did not matter the voting system used by the indigenous Papuans because the essence in the General Election process was that everyone could exercise their voting rights directly, freely, and confidentially. With the implementation of the General Election the noken system and / or the binding system does not provide guarantees and legal certainty to the constitutional rights of the voters to determine for themselves who they think is best based on their rational logic. Honesty does not only mean that no General Election provisions have been violated or that no vote has been manipulated. Honesty must also be interpreted as the system which best enables the people to elect candidates according to conscientious considerations based on the candidate's capacity and integrity.